ANALISIS PENGARUH LAJU ALIRAN MASSA TERHADAP KOEFISIEN PERPINDAHAN PANAS RATA-RATA PADA PIPA KAPILER DI MESIN REFRIGERASI FOCUS 808 - Basri, Basri (Jurnal MEKANIKAL, 2011)
This study aimed to obtain the influence of the mass flow rate of heat transfer coefficient on average that occurs in the capillary tube and the relationship between mass flow with heat transfer coefficient on average in the capillary tube. This research was conducted at the University Engineering Laboratory Cooling Tadulako. Test methods used in the study is testing them experimentally. Data were collected by taking a direct test data on test equipment. Data were analyzed theoretically based on the experimental test data. The results of this study, namely that the refrigerant mass flow rate affect the heat transfer coefficient on average that occurs in the capillary tube is in the form of equation (see full text) Â Â